Pengaruh Komposisi Gum Arabic Terhadap Konsistensi Padatan Tinta Organik Batang Kayu Secang Dalam Uji Solid Content - Zain Sultan Sultan Mahmuda; Heribertus Rudi Kusumantoro; Yoga Putra Pratama (Politeknik Negeri Ketapang, 2025)
This study investigates the effect of gum arabic composition on the solid content of organic ink made from sappan wood (Caesalpinia sappan) as a natural dye. The study uses a quantitative method with an experimental approach. The main focus of this research is the solid content test, which is important for determining the quality and durability of organic inks. Variations of gum arabic were used as a binder in the ink formulation, with the tests conducted using screen printing on cotton combed fabric. The results indicate that the lower the composition of gum arabic used, the higher the solid content obtained. The ink with the lowest gum arabic composition (5 grams) produced the highest solid content at 78.79%, compared to 75.00% for 10 grams and 60.00% for 15 grams of gum arabic. Additionally, physical characteristics such as color intensity and viscosity were also influenced by the solid content, with darker colors and thicker textures observed as the solid content increased. These findings contribute to the development of more eco-friendly organic inks with improved stability and performance, supporting the sustainability trend in the printing industry.